Fossil cocoons associated with a dinosaur egg from Patagonia, Argentina - Genise, Jorge Fernando (2011)
Eight fossil (Cretaceous) insect cocoons were discovered within the infillings of a broken dinosaur egg of a clutch from a Patagonian locality. Cocoons are considered to be in situ based on detailed preservation of thin, delicate walls with surface texture, infillings that are similar to the surrounding rock matrix and the clustered distribution of cocoons in only one egg out of the clutch of five eggs. According to the shape, size, and thin wall with surface texture, the cocoons are interpreted as having been produced by wasps. The wasps may have been attracted to the egg because of the presence of scavenging insects feeding on the decaying organic matter, or they may have been attracted to spiders feeding on the scavenging insects. In either scenario, after attacking the insects or spiders inside the sand infillings of the egg, the wasp larvae produced the cocoons described herein. The presence of wasps, which are at the top of the scavenging food webs, suggests that a complex community of invertebrates would have developed around rotten dinosaur eggs.